Implementasi Metode Taḥfīẓul Quran abaq, Sabqi, Manzil Di Marhalah Mutawasithah Dan Tsanawiyah Putri Pondok Pesantren Imam Bukhari Tahun Pelajaran 2010-2014 - Haironi, Adi, Dr.ArI Anshori, M.Ag, Dr. Muthoifin, M.Ag (2016)
Boarding school is an institution where the spread of Islamic knowledge occurs and becomes an educational institution which can survive for a long time and evolve until now. Boarding school has an important role in improving people's intelligence and personality. They usually held formal education as well as Islamic education which is done informally, especially in the memorization of Koran program. One of these educational institutions is Imam Bukhari Boarding School Karanganyar. In this study, the researcher would try to conduct a research in Marhalah Mutawasithah (Junior High School) and Tsanawiyah (Senior High School) because both of these institutions strive to reach maximum target level. This study was conducted to determine the implementation of memorization "sabaq, sabqi, manzil" in Marhalah Mutawasithah (Junior High School) and Tsanawiyah (Senior High School) and the implications that arise from the program. The research design for this study is a qualitative research. It describes the data collected as the scope of the research and includes the type of field research (field research) .The type of this study is case study, because the object of the study is the learning method of Tahfiz al-Quran (Memorization of Koran) in Marhalah Mutawasithah (Junior High School) and Tsanawiyah (Senior High School). The data that had been collected was analyzed by organizing the data. The data was collected by using documentation, observation and interviews. All data that had been collected was organized, sorted, grouped and categorized so the researcher can discover the appropriate theme in learning methods of Tahfiz al-Quran (Memorization of Koran) in Marhalah Mutawasithah (Junior High School) and Tsanawiyah (Senior High School). Based on the analysis, the researcher concludes that the method applied in teaching Tahfiz al-Quran in Marhalah Mutawasithah and Marhalah Tsanawiyah is effective and efficient. Then with "sabaq, sabqi, manzil" memorization methods bring miraculous implications for helping students to understand and memorize the basics of Islamic teachings in the form of verses of the Koran, thus indirectly increases Islamic knowledge capabilities. In the case of muamalah (human to human interaction), the influence of memorization of Koran is clearly seen in which students' character seems better as the reflection of the implication of the verses of the Koran. In addition, the students are more eager to complete the recitation of 30 chapters of Koran.This can be seen in the last five years, the number of students who can complete memorizing 30 chapters is always increasing. The achievement target rote of Marhalah Tsanawiyah his higher than the achievement target of Marhalah Mutawasithah.